Improved determination of microseismic source location using a simplex technique - Vance, J.B.; Hassani, F.P.; Mottahed, P. (IEEE transactions on industry applications, 1988)
The monitoring of microseismic activity in geological formations of underground mines is discussed. The accuracy of a particular monitoring technique is subject to limitations of measurement precision, and errors in the determination of the correct phase of the incoming signal associated with the first arrival of the seismic wave. The value of the simplex technique for microseismic monitoring is illustrated through the presentation of experimental results in the determination of source location for a series of known-source test blasts. It is concluded that a careful analysis of the errors affecting each particular microseismic installation is a necessary step in understanding the capabilities of this particular system.< >